iStar (i*): An interactive star coordinates approach for high-dimensional data exploration - Garcia Zanabria G. (2016)
We would like to thank the financial support from the National Council for Science, Technology and Technological Innovation - CONCYTEC, Peru (grant FONDECYT 011-2013 Master Program), the São Paulo Research Foundation - FAPESP (grants #2013/00191-0 and #2011/22749-8) and the National Counsel of Technological and Scientific Development - CNPq, Brazil (grant #302643/2013-3).